THE EFFECT OF NUTRITIONAL STATUS ON GROSS MOTOR SKILL IN PRE SCHOOL CHILDREN - Tutfah Razzak Fitriari; Ahmad Suryawan; Sulistiawati Sulistiawati (UNIVERSITAS AIRLANGGA, 2021)
Background and Purpose : Nutritional status is one aspect that influences children’s development. Children whose nutritional needs are not being met are at risk of experiencing developmental disorders, where one aspect of development that is affected is their gross motor skills. Indonesia has a number of malnutrition up to 17.7% with a motor disorder rate of 13-18%. This study aims to analyze the relationship between nutritional status and gross motor skill status of children aged 60-72 months in Islam Al karomah Surabaya Kindergarten. Methods : This study use obervational analytic method with cross sectional design study design. The sample in this study were children who attend Islamic Al Karomah kindergarten in Surabaya. The number of samples was 40 respondents in the Islam Al Karomah Surabaya Kindergarten. The sampling technique of this study was total sampling with nutritional status as independent variable and gross motor skill status as dependent variable. The instuments of this study are Z-Scores (Body Mass Index for age) and Developmental Pre Screening Questionnaire for collecting data and was analyzed by Fisher’s Exact test (a=0.05). Results : Almost all of the children with normal gross motor skills (78.1%) have a normal nutritional status with the results of Fisher’s Exact analysis shown p value = 0.007 (p<0.05). Conclusion : there is a relationship between the nutritional status and gross motor skill status of children aged 60-72 months in Islam Al karomah Surabaya Kindergarten.